2020
DOI: 10.3389/fimmu.2020.00868
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 in the Combination Immunotherapy of Cancer

Abstract: We completed clinical trials of rhIL-15 by bolus, subcutaneous, and continuous intravenous infusions (CIV). IL-15 administered by CIV at 2 mcg/kg/day yielded a 38-fold increase in 10-day number of circulating NK cells, a 358-fold increase in CD56 bright NK cells and a 5.8-fold increase in CD8 T cells. However, IL-15 preparations administered as monotherapy were ineffective, due to actions of immunological checkpoints and due to the lack of tumor specific targeting by NK cells. To circumvent checkpoints, trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 86 publications
1
142
0
1
Order By: Relevance
“…NCT01875601) in which the cytokine is administered employing different dosing regimens, including intravenous bolus and subcutaneous and continuous infusion of monomeric sIL-15 both in adult and pediatric solid tumors. [90][91][92][93][94] There is also a number of clinical trials (NCT01727076, NCT01885897, NCT02523469), based on the utilization of an IL-15N72D/IL-15Rα-Fc super-agonist complex, termed N-803 (formerly Alt-803, from NantKwest, Culver City, California, USA) supposed to maximize expansion and priming of immune cells (NK and CD8 + T-cells). 95 96 However, in the latter setting a drawback rises from the rapid consumption of the injected IL-15 agonists due to the rapid and huge expansion of the target immune cells.…”
Section: Clinical Trials Rhil-15 Is Currently Under Investigation Inmentioning
confidence: 99%
“…NCT01875601) in which the cytokine is administered employing different dosing regimens, including intravenous bolus and subcutaneous and continuous infusion of monomeric sIL-15 both in adult and pediatric solid tumors. [90][91][92][93][94] There is also a number of clinical trials (NCT01727076, NCT01885897, NCT02523469), based on the utilization of an IL-15N72D/IL-15Rα-Fc super-agonist complex, termed N-803 (formerly Alt-803, from NantKwest, Culver City, California, USA) supposed to maximize expansion and priming of immune cells (NK and CD8 + T-cells). 95 96 However, in the latter setting a drawback rises from the rapid consumption of the injected IL-15 agonists due to the rapid and huge expansion of the target immune cells.…”
Section: Clinical Trials Rhil-15 Is Currently Under Investigation Inmentioning
confidence: 99%
“…IL-15 as a monotherapy for solid tumors is not as effective as expected ( 42 ). Two major strategies including IL-15 superagonist and combination therapy have been pursued to improve its therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 87%
“…Combination immunotherapy has been proposed to enhance the efficacy of IL-15 ( 42 ). MDSCs are predominant in 4T1 breast tumor and have been reported to associate with tumor burden or late stage breast tumor ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials evaluating IL-15, a low level of response was observed. To potentially overcome these poor responses, studies are being conducted to determine the potential of combining IL-15 or IL-15/IL-15Rα with other immune modifiers, including checkpoint inhibitors [ 40 , 41 , 42 ]. Interestingly, in the pIL-12 clinical trials, patients who had a poor response were observed to have elevated tumor levels of PD-1 and PD-L1 [ 34 , 43 ].…”
Section: Discussionmentioning
confidence: 99%